Evaluación de tres bioestimulantes foliares en el cultivo de haba sometido a dos niveles de fertilización edáfica en la zona de Huaca, provincia del Carchi - López Velasco, Mariana Alicia (2011)
This research studied the effect of soil bio-stimulants and foliar fertilizers on vegetative growth and crop production of beans. Huaca locally Region San Pedro de Huaca, Carchi province, with geographic coordinates 0 ˚ 37 'North Latitude. 77 ˚ 43 'West Longitude and 2 950 m.s.n.m. with the objective of evaluating the physiological effects of cultivation of beans subjected to different treatments, determine the most effective dose in both bioestimulantes as soil fertilizer, analyzing economic treatments carried out. The design used was randomized complete block (RCBD) with factorial A x B +1, with seven treatments and four replications. The total area of 1029.50 m2 experimental counted, each plot was 24 m2 and a useful area of 14.40 m2, the separation between replicates and plots was 1 m. Variables were evaluated: plant height at 30, 60. 90 days after emergence and at harvest, number of pods per plant, pod length, number of grains per plant, grain weight per plant, yield per hectare.